Environmental Pollution and Human Health: Integrated Assessment and Sustainable Solutions in Central Asia - D., Kholov Y.; Z., Sharipova; F., Farmonova; Sh., Komiljonova (American Journal of Biodiversity, 2026)
Environmental pollution has become one of the most critical global challenges, significantly affecting human health and ecosystem stability. Air, water, and soil pollution contribute to the spread of diseases, reduce life expectancy, and increase healthcare burdens. This study provides a comprehensive assessment of the relationship between environmental pollution and human health, focusing on Central Asia and Uzbekistan. The research integrates environmental analysis, epidemiological data, and sustainability approaches. The findings reveal that environmental degradation directly contributes to respiratory diseases, cardiovascular disorders, and waterborne illnesses. The study also identifies key sources of pollution and proposes sustainable solutions, including renewable energy adoption, improved waste management, and environmental policy reforms. The results highlight the need for integrated environmental and health strategies to ensure long-term sustainability.